2011
DOI: 10.1002/mc.21868
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in GSTM1 and XPD genes predict clinical outcome in advanced oral cancer patients treated with postoperative radiotherapy

Abstract: Polymorphisms in metabolic and DNA repair genes may alter protein function, consequently affecting patients' response to chemo/radiotherapy. We retrospectively assessed whether polymorphisms of glutathione-S-transferase genes GSTM1 (deletion), GSTT1 (deletion), GSTP1 (Ile105Val, rs1695), and DNA repair genes hOGG1 (Ser326Cys, rs1052133), XRCC1 (Arg194Trp, rs1799782, and Arg399Gln, rs25487), XPD (Asp312Asn, rs1799793, and Lys751Gln, rs13181) can predict clinical outcome in 187 oral squamous cell carcinoma patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 48 publications
1
27
2
Order By: Relevance
“…312 (Asp to Asn) and 751 (Lys to Gln) were the main two polymorphisms that induce amino acid changes in the proteins (Shen et al, 1998). The associations of the Lys751Gln polymorphism in XPD gene with the prognosis of various types of cancer have been widely reported in cancer epidemiologic studies, such as colorectal cancer, advanced lung cancer, oral cancer and pancreatic cancer (Giovannetti et al, 2011;Biason et al, 2012;Chen et al, 2012;Mahimkar et al, 2012;Slyskova et al, 2012). In our study, we have found polymorphism in XPD Lys751Gln is related to the prognosis of HCC, which has provided evidence that the XPD protein influences the overall survival of HCC through NER pathway.…”
Section: Discussionsupporting
confidence: 68%
“…312 (Asp to Asn) and 751 (Lys to Gln) were the main two polymorphisms that induce amino acid changes in the proteins (Shen et al, 1998). The associations of the Lys751Gln polymorphism in XPD gene with the prognosis of various types of cancer have been widely reported in cancer epidemiologic studies, such as colorectal cancer, advanced lung cancer, oral cancer and pancreatic cancer (Giovannetti et al, 2011;Biason et al, 2012;Chen et al, 2012;Mahimkar et al, 2012;Slyskova et al, 2012). In our study, we have found polymorphism in XPD Lys751Gln is related to the prognosis of HCC, which has provided evidence that the XPD protein influences the overall survival of HCC through NER pathway.…”
Section: Discussionsupporting
confidence: 68%
“…ERCC2 is an evolutionary conservative DNA helicase, which is an important link of nucleotide excision repair pathways, involved in nucleotide excision repair and bases of transcription. Studies have found that ERCC2 RS13181 can predict clinical outcome in oral squamous cell carcinoma patients and in soft-tissue sarcoma patients treated with postoperative radiotherapy (Mahimkar et al, 2012;Szkandera et al, 2013). However, in patients with rectal cancer, we found that no association between RS13181 and response with a neoadjuvant radiochemotherapy.…”
Section: Discussioncontrasting
confidence: 68%
“…Thus, DNA repair mechanisms are very important for maintaining genome integrity and preventing carcinogenesis. Base excision repair (BER) pathway is the key mechanism involved in repairing small base lesions in DNA that are the result of oxidation and alkylation damage (Hoeijmakers, 2001;Mahimkar et al, 2012), and was closely associated with lung cancer development (Qian and Massion, 2008). SNPs in susceptible genes have been increasingly emphasized on the grounds that XRCC1 is considered a crucial scaffold protein closely associated with the base excision repair pathway (Campalans et al, 2005).…”
Section: Discussionmentioning
confidence: 99%